Integrative Korean Medicine Treatment for Obesity and Overweight in Children and Adolescents: A Multicenter Retrospective Chart Review Study - Seo HS; Lee SH; Yim MH; Jeong YK; Chang GT; Ahn YJ; Lee JD; Chung WS; Ahn SY; Ahn YM; Lee BC; Noh JW; et al. (Diabetes, Metabolic Syndrome and Obesity, 2023)
Hae Sun Seo,1,* Sun Haeng Lee,1,* Mi Hong Yim,2 Yoon Kyoung Jeong,3 Gyu Tae Chang,3 Ye-Ji Ahn,4 Jae Dong Lee,5 Won Seok Chung,6 Se Young Ahn,7 Young Min Ahn,7 Byung Cheol Lee,7 Ji-Won Noh,7 Boram Lee8 1Department of Korean Pediatrics, College of Korean Medicine, Kyung Hee University, Kyung Hee University Medical Center, Seoul, South Korea; 2Digital Health Research Division, Korea Institute of Oriental Medicine, Daejeon, South Korea; 3Department of Korean Pediatrics, College of Korean Medicine, Kyung Hee University, Kyung Hee University Hospital at Gangdong, Seoul, South Korea; 4Haeundae Hamsoa Korean Medicine Clinic, Busan, South Korea; 5Department of Acupuncture & Moxibustion Medicine, College of Korean Medicine, Kyung Hee University, Kyung Hee University Medical Center, Seoul, South Korea; 6Department of Korean Rehabilitation Medicine, College of Korean Medicine, Kyung Hee University, Kyung Hee University Medical Center, Seoul, South Korea; 7Department of Internal Medicine, College of Korean Medicine, Kyung Hee University, Kyung Hee University Medical Center, Seoul, South Korea; 8KM Science Research Division, Korea Institute of Oriental Medicine, Daejeon, South Korea*These authors contributed equally to this workCorrespondence: Boram Lee, KM Science Research Division, Korea Institute of Oriental Medicine, 1672 Yuseong-daero, Yuseong-gu, Daejeon, 34054, South Korea, Tel +82-42-868-9622, Fax +82-42-868-9395, Email qhfka9357@kiom.re.krIntroduction: Integrative Korean medicine treatment (IKM), including herbal medicine (HM) and acupuncture, has been widely used for obesity and overweight in children and adolescents in South Korea. We investigated the real-world usage status and the potential effect of the IKM for obesity and overweight in children and adolescents.Methods: Multicenter medical charts were retrospectively reviewed of obese and overweight children and adolescents who visited Korean medicine institutions with the goal of weight control for the first time and received IKM, to analyze the usage status and effect of IKM. We defined IKM responders as those with an improved obesity grade on the body mass index (BMI) percentile and analyzed their characteristics.Results: Medical charts of 209 patients (183 obese and 26 overweight) with a mean age of 11.45 years were examined. Patients visited the institution a mean of 5.95 times, and HM alone and HM plus acupuncture were frequently used IKM. HM was prescribed to 205 patients, 167 of whom received an HM prescription containing Ephedrae Herba. An HM of the decoction type was prescribed to 189 patients, and the average treatment duration was 76.54 days. After IKM, the percentile and z-score of BMI and weight significantly declined and height percentile and z-score were significantly enhanced, without serious adverse events. In the IKM responders, age, and the proportion of girls and overweight were significantly higher, and the percentile and z-score of height, weight, and BMI were significantly lower.Conclusion: This is the first study to examine the real-world usage of IKM for obesity and overweight in children and adolescents. A significant improvement in obesity-related outcome measures after IKM, illustrated the potential effect of IKM.Keywords: pediatric obesity, childhood overweight, traditional Korean medicine, herbal medicine, acupuncture